Development of integrated thematic teaching materials using a contextual approach in increasing student self-control to prevent Covid-19 transmission in elementary schools - Daryus, Muthyara; Firman, Firman; Mulya, Jumiatul (International Journal of Applied Counseling and Social Sciences, 2023)
The spread of Covid-19 is rapidly expanding to all parts of the world, causing changes in activity patterns in all sectors of life, one of which is the education sector. This study aims to describe and develop integrated thematic teaching materials using a contextual approach to improve the self-control of fifth grade students at SD Negeri 21 Lubuk Lintah which are valid, practical, and effective. This type of research is development using a modified 4-D model. Based on the results of the study, the average score for the assessment of integrated thematic teaching materials uses a contextual approach with a validity value of 89.4% in the valid category. From the results of practicality by the teacher obtaining results of 87.5% in the practical category and from the results of practicality by students obtaining results of 84.5% in the practical category. The results of the effectiveness of using teaching materials get an average of 0.74 in the effective category. It can be concluded that the thematic teaching materials use a contextual approach to increase self-control of fifth grade elementary school students which is valid, practical, and effective and can increase students' self-control in preventing Covid-19.